Operational monitoring windows from cumulative rainfall to chlorophyll-a in subtropical reservoirs - Jingxin Wei; Peiliang Chen; Xingcheng Fu; Jie Ling; Bingqing Xiao; Xuedong Xie; Bozhu Huang; Jingyi Cen; Songhui Lu (Environmental Monitoring and Assessment, 2026)

Genome-wide association and genomic selection studies on feed efficiency with fishmeal-free feed in large yellow croaker (Larimichthys crocea) - Gongsi Wang; Yingbo Yuan; Xiaotong Li; Ranxin Fu; Xingcheng Zhu; Zhenye Zhao; Yuhan Jin; Sen Zhang; Peng Ren; Lining Zhang; Qinghui Ai; Ming Fang; et al. (Aquaculture, 2025)

Intestinal microbiota was closely related to feed efficiency of Larimichthys crocea fed two fishmeal-free diets - Xiaotong Li; Gongsi Wang; Ranxin Fu; Xingcheng Zhu; Peng Ren; Lining Zhang; Qinghui Ai; Yunzhang Sun; Zhiyong Wang (Aquaculture, 2025)

Detection and Tracking of Low-Frame-Rate Water Surface Dynamic Multi-Target Based on the YOLOv7-DeepSORT Fusion Algorithm - Xingcheng Han; Shiwen Fu; Junxuan Han (Journal of Marine Science and Engineering, 2024)
This study aims to address the problem in tracking technology in which targeted cruising ships or submarines sailing near the water surface are tracked at low frame rates or with some frames missing in the video image, so that the tracked targets have a large gap between frames, leading to a decrease in tracking accuracy and inefficiency. Thus, in this study, we proposed a water surface dynamic multi-target tracking algorithm based on the fusion of YOLOv7 and DeepSORT. The algorithm first introduces the super-resolution reconstruction network. The network can eliminate the interference of clouds and waves in images to improve the quality of tracking target images and clarify the target characteristics in the image. Then, the shuffle attention module is introduced into YOLOv7 to enhance the feature extraction ability of the target features in the recognition network. Finally, Euclidean distance matching is introduced into the cascade matching of the DeepSORT algorithm to replace the distance matching of IOU to improve the target tracking accuracy. Simulation results showed that the algorithm proposed in this study has a good tracking effect, with an improvement of 9.4% in the improved YOLOv7 model relative to the mAP50-95 value and an improvement of 13.1% in the tracking accuracy in the DeepSORT tracking network compared with the SORT tracking accuracy.